2016
DOI: 10.1186/s13722-016-0063-8
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted academic detailing program to increase pharmacotherapy for alcohol use disorder: interrupted time series evaluation of effectiveness

Abstract: BackgroundActive consideration of effective medications to treat alcohol use disorder (AUD) is a consensus standard of care, yet knowledge and use of these medications are very low across diverse settings. This study evaluated the overall effectiveness a multifaceted academic detailing program to address this persistent quality problem in the US Veterans Health Administration (VHA), as well as the context and process factors that explained variation in effectiveness across sites.MethodsAn interrupted time seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 22 publications
1
35
0
Order By: Relevance
“…19 Other potential strategies to improve uptake and referral to agonist treatment among criminal justice staff could include academic detailing programs—that is, [please provide]—which have been shown to improve the adoption of pharmacotherapy for substance use disorders in other settings. 40 Beyond training and culture change, it is essential that policies be put in place to ensure that justice-involved people have the right and ability to access agonist treatment. A 2015 federal regulation now prohibits drug courts that receive federal funds from denying participants access to or continuity of agonist treatment.…”
Section: Discussionmentioning
confidence: 99%
“…19 Other potential strategies to improve uptake and referral to agonist treatment among criminal justice staff could include academic detailing programs—that is, [please provide]—which have been shown to improve the adoption of pharmacotherapy for substance use disorders in other settings. 40 Beyond training and culture change, it is essential that policies be put in place to ensure that justice-involved people have the right and ability to access agonist treatment. A 2015 federal regulation now prohibits drug courts that receive federal funds from denying participants access to or continuity of agonist treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Academic detailing is a multi-facetted educational outreach program that in which prescribers are presented with information about the targeted medications in a series of face-to-face visits with trained health care professionals. A recent evaluation of this multi-facetted program within VA found a 3.3% positive increase in absolute rates (5.0% to 8.3%) of prescribing of pharmacotherapy for AUD across settings (Harris et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…For example, one study found that of the 11 million people in the United States with AUD, only 674,000 received psychopharmacological treatment (Mark et al 2009). Furthermore, treatment availability and the type of treatment provided can vary based on geography and, in the United States, insurance coverage (Hagedorn et al 2016;Mark et al 2015), including formulary restrictions (Harris et al 2013). In a systematic literature review focused on this disparity, Hagedorn et al (2016) identified contributing factors at the level of patients (e.g., lack of awareness of treatment options) and clinicians (e.g., perceived low demand and low confidence in the efficacy of pharmacotherapy).…”
Section: Rationalementioning
confidence: 99%
“…Furthermore, treatment availability and the type of treatment provided can vary based on geography and, in the United States, insurance coverage (Hagedorn et al 2016;Mark et al 2015), including formulary restrictions (Harris et al 2013). In a systematic literature review focused on this disparity, Hagedorn et al (2016) identified contributing factors at the level of patients (e.g., lack of awareness of treatment options) and clinicians (e.g., perceived low demand and low confidence in the efficacy of pharmacotherapy). Other clinician barriers to prescribing medications for AUD include an inability to provide suitable psychosocial co-interventions and lack of familiarity with medications (Harris et al 2013;O'Malley and O'Connor 2011).…”
Section: Rationalementioning
confidence: 99%
See 1 more Smart Citation